Enhancing Data Governance with Real-Time Analytics in Oil Production Forecasting - Nihitha Sallapalli, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative impact of real-time analytics on oil production forecasting in the oil and gas industry. It discusses the shift from traditional batch processing to real-time data analysis, highlighting the limitations of batch processing and the benefits of real-time analytics. The article examines how advanced data processing platforms enable more effective data governance and faster insights, leading to improved decision-making, enhanced operational efficiency, and increased production. It also delves into the role of real-time analytics in strengthening compliance and accountability through automated data collection, validation, and consistent data handling. The article presents various case studies and numerical data demonstrating the significant improvements in forecasting accuracy, anomaly detection, and regulatory compliance achieved by implementing real-time analytics systems.
Keywords: Real-time analytics; Oil production forecasting; Data governance; Machine learning; Compliance and accountability